Psycholinguistic Aspects of Teaching a Foreign Language in an Electronic System for the Formation of Speech Skills - A. K. Dadykin; A. K. Al-Subaih; M. A. Al-Masoodi (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Mastering foreign languages is a deep process that covers several areas of human activity, including not only psycholinguistics, but also cognitive psychology, while affecting the area of interaction between consciousness and the unconscious. In the XXI century, a new technological basis has appeared, combining information and communication technologies and artificial intelligence. The systematic approach serves as a mechanism that allows combining modern technologies with those methods of teaching foreign languages that were previously available only to a narrow circle of specialists. The purpose of the research is to develop a training system created on the basis of modern information and communication technologies for acquiring speech skills of foreign language proficiency by adults on a massive scale. The article provides a brief description of the psycholinguistic aspects that can significantly reduce the duration of training. The proposed learning management system should work in combination with a methodologically precisely integrated linguistic system and ensure the formation of the speech zone of the acquired language in the adult learner’s mind during the learning process. The main result can be considered a conceptual solution to the problem of simultaneous interaction of the language system and the means of information and communication technologies that ensure the sustainable formation of foreign language thinking of adults in the process of developing professional and language skills, presented at the system level. And the introduction of the student’s psyche directly into the educational process management circuit should be considered as a new direction in the development of e-learning.